COVID-19 and Rheumatology - Ansh Bhatia; Latika Gupta; Vikas Agarwal (Dr. Annil Mahajan, 2021)
The pandemic caused by the SARS-Cov-2 coronavirus causing COVID-19 has been an unmitigated disaster that has resulted in a litany of clinical challenges. COVID-19 can present with myriad manifestations, some regularly encountered in rheumatology. COVID-19 can particularly be confused with rheumatic disorders in the presence of frank arthritis, cutaneous vasculitis rashes, thrombosis, and frank muscle weakness, typical rashes of dermatomyositis, and acute interstitial pneumonitis, which leads to suspicion of autoimmune rapidly progressive lung disease.